2013
DOI: 10.1186/1471-2407-13-223
|View full text |Cite
|
Sign up to set email alerts
|

High CRP values predict poor survival in patients with penile cancer

Abstract: BackgroundHigh levels of circulating C-reactive protein (CRP) have recently been linked to poor clinical outcome in various malignancies. The aim of this study was to evaluate the prognostic significance of the preoperative serum CRP level in patients with squamous cell carcinoma (SCC) of the penis.MethodsThis retrospective analysis included 79 penile cancer patients with information about their serum CRP value prior to surgery who underwent either radical or partial penectomy at two German high-volume centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
4
27
0
Order By: Relevance
“…C-reactive protein is an acute-phase reactant that responds to the tumour microenvironment, causing tumour cell death and local tissue damage [25], and high levels of this protein have been linked to cancer risk and/or progression in various malignancies [13][14][15]. In the present study, elevated CRP levels were associated with progressive tumour characteristics, including ENE (P < 0.001), pelvic LNM (P = 0.007), pathological tumour status (P = 0.002), and pathological nodal status (P < 0.001; Table 2), consistent with several previous studies [16,17]. Because these pathological characteristics are of utmost prognostic importance in penile carcinoma [1][2][3]22,23], an elevated CRP level may be predictive of more aggressive and progressive disease [16,17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…C-reactive protein is an acute-phase reactant that responds to the tumour microenvironment, causing tumour cell death and local tissue damage [25], and high levels of this protein have been linked to cancer risk and/or progression in various malignancies [13][14][15]. In the present study, elevated CRP levels were associated with progressive tumour characteristics, including ENE (P < 0.001), pelvic LNM (P = 0.007), pathological tumour status (P = 0.002), and pathological nodal status (P < 0.001; Table 2), consistent with several previous studies [16,17]. Because these pathological characteristics are of utmost prognostic importance in penile carcinoma [1][2][3]22,23], an elevated CRP level may be predictive of more aggressive and progressive disease [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Elevated CRP levels before surgery can serve as a diagnostic marker and a marker of poor prognosis in penile cancer [16,17]. Similarly, several studies have shown that SCC-Ag level, which might also serve as a sensitive marker of disease progression, is correlated with tumour burden in penile cancer [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CRP may indicate inflammation. Previous studies have demonstrated that an increased level of CRP may be associated with poorer prognosis in patients with tumors, including ovarian cancer, penile cancer and non-small cell lung cancer (36)(37)(38). In addition, malabsorption and malnutrition may be associated with decreased survival time in various tumors, including esophageal squamous cell carcinomas and endometrial cancer (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated C-reactive protein (CRP) has been reported to be associated with nodal metastasis and poorer cancerspecific survival (CSS) [9,10], and a high neutrophillymphocyte ratio (NLR) has also been shown to predict poor CSS in patients with penile cancer [11]. Another potential biomarker, the absolute lymphocyte count-absolute monocyte count ratio (LMR) has been shown to be able to predict clinical outcomes of patients with cancer, including colorectal cancer, sarcoma and lymphoid neoplasms [12][13][14].…”
Section: Introductionmentioning
confidence: 99%